Adipose overexpression of heme oxygenase-1 does not protect against high fat diet-induced insulin resistance in mice. - Jun-Yuan Huang; Ming-Tsai Chiang; Lee-Young Chau (PLoS ONE, 2013)
Heme oxygenase-1 (HO-1) is a stress-responsive enzyme with potent anti-oxidant and anti-inflammatory activities. Previous studies have shown that systemic induction of HO-1 by chemical inducers reduces adiposity and improves insulin sensitivity. To dissect the specific function of HO-1 in adipose tissue, we generated transgenic mice with adipose HO-1 overexpression using the adipocyte-specific aP2 promoter. The transgenic (Tg) mice exhibit similar metabolic phenotype as wild type (WT) control under chow-fed condition. High fat diet (HFD) challenge significantly increased the body weights of WT and Tg mice to a similar extent. Likewise, HFD-induced glucose intolerance and insulin resistance were not much different between WT and Tg mice. Analysis of the adipose tissue gene expression revealed that the mRNA levels of adiponectin and interleukin-10 were significantly higher in chow diet-fed Tg mice as compared to WT counterparts, whereas HFD induced downregulation of adiponectin gene expression in both Tg and WT mice to a similar level. HFD-induced proinflammatory cytokine expression in adipose tissues were comparable between WT and transgenic mice. Nevertheless, immunohistochemistry and gene expression analysis showed that the number of infiltrating macrophages with preferential expression of M2 markers was significantly higher in the adipose tissue of obese Tg mice than WT mice. Further experiment demonstrated that myeloid cells from Tg mice expressed higher level of HO-1 and exhibited greater migration response toward chemoattractant in vitro. Collectively, these data indicate that HO-1 overexpression in adipocytes does not protect against HFD-induced obesity and the development of insulin resistance in mice.